2011
DOI: 10.1177/1040638711406974
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Anaplasma phagocytophilum in Brazilian dogs by real-time polymerase chain reaction

Abstract: Anaplasma phagocytophilum was detected in dogs from Brazil in the municipalities of Seropédica and Itaguaí, Rio de Janeiro state, by real-time polymerase chain reaction (PCR) using SYBR Green to detect the amplification. Of 253 samples, 18 (7.11%) were positive, with a threshold cycle (Ct) ranging from 31 to 35 cycles. The PCR product from a positive sample was cloned and sequenced. The sequence obtained demonstrated 100% identity with other A. phagocytophilum sequences published in the GenBank database. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 17 publications
(31 reference statements)
0
30
0
1
Order By: Relevance
“…nas amostras testadas pela PCR. Ao contrário de N. risticii, espécies filogeneticamente próximas ou idênticas a A. phagocytophilum já foram detectadas em cães, cervídeos e aves no Brasil (Santos et al, 2011;Machado et al, 2012;Secchi et al, 2012 (Salvagni et al, 2010). No presente estudo, 39,6% dos animais foram reagentes a antígenos de Ehrlichia spp.…”
Section: Discussionunclassified
“…nas amostras testadas pela PCR. Ao contrário de N. risticii, espécies filogeneticamente próximas ou idênticas a A. phagocytophilum já foram detectadas em cães, cervídeos e aves no Brasil (Santos et al, 2011;Machado et al, 2012;Secchi et al, 2012 (Salvagni et al, 2010). No presente estudo, 39,6% dos animais foram reagentes a antígenos de Ehrlichia spp.…”
Section: Discussionunclassified
“…Although dogs infected with A. platys and A. phagocytophilum usually present mild symptoms or are asymptomatic (HARRUS et al, 1997;KOHN et al, 2008;RAR;GOLOVLJOVA, 2011), some cases may be serious or fatal, particularly when co-infections are involved (DANTAS-TORRES, 2008). The confirmation of the occurrence of E. ewingii ) and A. phagocytophilum (SANTOS et al, 2011) in dogs from Minas Gerais and Rio de Janeiro, respectively, showed that other Anaplasmataceae agents circulate among dogs in Brazil, although the vector tick species involved in these transmission routes remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Anaplasma platys, a bacterium that parasitizes platelets, causing canine cyclic thrombocytopenia (COHN, 2003), has also been reported in dogs in Brazil (DAGNONE et al, 2009). Furthermore, A. phagocytophilum also has been detected molecularly in dogs in the state of Rio de Janeiro, Brazil (SANTOS et al, 2011). Although dogs infected with A. platys and A. phagocytophilum usually present mild symptoms or are asymptomatic (HARRUS et al, 1997;KOHN et al, 2008;RAR;GOLOVLJOVA, 2011), some cases may be serious or fatal, particularly when co-infections are involved (DANTAS-TORRES, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, E. chaffeensis and A. phagocytophilum have only been detected in marsh deer (Blastocerus dichomotus) (Machado et al 2006), and dogs (Santos et al 2011) in Brazil, respectively. E. chaffeensis DNA found in the hawk in our study was closely related to E. chaffeensis found in Brazilian marsh deer (Machado et al 2006) in the 16S rRNA phylogenetic tree.…”
mentioning
confidence: 99%
“…In Brazil, Ehrlichia chaffeensis and Anaplasma phagocytophilum have been detected in Brazilian marsh deer (Blastocerus dichotomus) (Machado et al 2006) and dogs (Santos et al 2011), respectively. Regarding the occurrence of ehrlichiosis among humans in Brazil, only serological studies have been reported (Calic et al 2004;Costa et al 2005).…”
mentioning
confidence: 99%